Amending the Constitution of the Republic of Iraq (2005): Constitution, amendment, parliament, extraordinary amendment, normal amendment, proposal of the amendment, referendum - Mohammad Taha Hussein AL-Huseini, (Technium Social Sciences Journal, 2020)
The authority that have the right to amend the constitution have to be restricted to two points: the first is to abide by the restrictions which the constitutional legislator imposed for the amendment, and the second is that the amendment should goes through the stages stipulated by it in the constitutional document. Both are found in the Iraqi constitution amendment, so the constitutional legislator imposed a set of restrictions on the amendment, which must be started with the proposal, the initiative approval and finally the final approval, whether the amendment is normal or extraordinary; each has its terms of success which may cause the difference between them.